Principles of Islamic International Criminal Law A Comparative Search - Malekian, Farhad (Brill, 2011)
The goal of this book is to minimize the misunderstandings and conflicts between International law and Islamic law. The objective is to bring peace into justice and justice into peace for the prevention of violations of human rights law, humanitarian law, international criminal law, and impunity.
Description based on print version record.
KU Select 2016 Backlist Collection
Keywords: Political Science; Political science; Electronic books